Carotid Plaque Inflammation Imaged by PET and Prediction of Recurrent Stroke at 5 Years. (7th December 2021) - McCabe, John Joseph; Camps-Renom, Pol; Giannotti, Nicola; McNulty, Jonathan P.; Coveney, Sarah; Murphy, Seán; Barry, Mary; Harbison, Joseph; Cronin, Simon; Williams, David; Horgan, Gillian; Dolan, Eamon; et al.
Abstract : Background and Objectives: To determine whether carotid plaque inflammation identified by 18 F-fluorodeoxyglucose ( 18 FDG)-PET is associated with late (5-year) recurrent stroke. Methods: We did an individual-participant data pooled analysis of 3 prospective studies with near-identical study methods. Eligible patients had recent nonsevere (modified Rankin Scale score ≤3) ischemic stroke/TIA and ipsilateral carotid stenosis (50%–99%). Participants underwent carotid 18 FDG-PET/CT angiography ≤14 days after recruitment. 18 FDG uptake was expressed as maximum standardized uptake value (SUVmax ) in the axial single hottest slice of symptomatic plaque. We calculated the previously validated Symptomatic Carotid Atheroma Inflammation Lumen-Stenosis (SCAIL) score, which incorporates a measure of stenosis severity and 18 FDG uptake. The primary outcome was 5-year recurrent ipsilateral ischemic stroke after PET imaging. Results: Of 183 eligible patients, 181 patients completed follow-up (98.9%). The median duration of follow-up was 4.9 years (interquartile range 3.3–6.4 years, cumulative follow-up period 901.8 patient-years). After PET imaging, 17 patients had a recurrent ipsilateral ischemic strokes at 5 years (recurrence rate 9.4%, 95% confidence interval [CI] 5.6%–14.6%). Baseline plaque SUVmax independently predicted 5-year ipsilateral recurrent stroke after adjustment for age, sex, carotid revascularization, stenosis severity, NIH Stroke Scale score, and diabetes mellitus (adjusted hazard ratio [HR] 1.98, 95% CI 1.10–3.56, p = 0.02 per 1–g/mL increase in SUVmax ). On multivariable Cox regression, SCAIL score predicted 5-year ipsilateral stroke (adjusted HR 2.73 per 1-point increase, 95% CI 1.52–4.90, p = 0.001). Discussion: Plaque inflammation–related 18 FDG uptake improved identification of 5-year recurrent ipsilateral ischemic stroke. Addition of plaque inflammation to current selection strategies may target patients most likely to have late and early benefit from carotid revascularization. Classification of Evidence: This study provides Class I evidence that in individuals with recent ischemic stroke/TIA and ipsilateral carotid stenosis, carotid plaque inflammation–related 18 FDG uptake on PET/CT angiography was associated with 5-year recurrent ipsilateral stroke.